2016
DOI: 10.5433/1679-0359.2016v37n3p1155
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sugarcane waste in the control of interrill erosion

Abstract: The cultivation of sugarcane uses different cropping systems that result in varying quantities of crop waste, this may influence soil erosion. The objective of this study was to evaluate the loss of soil and water, the infiltration rate, and soil surface roughness in an area cultivated with sugarcane (Saccharum spp.). Six treatments with different levels of plant waste were evaluated: sugarcane without plant waste; sugarcane with 4.0 Mg ha -1 of waste; sugarcane with 8.0 Mg ha -1 of waste; sugarcane with 12.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 21 publications
0
14
0
4
Order By: Relevance
“…Moreover, the maintenance of crop residues favors infiltration Johnson et al, 2016;Valim et al, 2016) and storage of water in the soil (Peres et al, 2010;Xiukang et al, 2015;Tormena et al, 2017). Peres et al (2010) observed that the presence of 15 Mg ha -1 of sugarcane straw covering the soil reduced water loss (0-20 cm layer) by approximately half when compared to uncovered soil.…”
Section: Ii) Crop Residues Vs Soil Physical Propertiesmentioning
confidence: 99%
“…Moreover, the maintenance of crop residues favors infiltration Johnson et al, 2016;Valim et al, 2016) and storage of water in the soil (Peres et al, 2010;Xiukang et al, 2015;Tormena et al, 2017). Peres et al (2010) observed that the presence of 15 Mg ha -1 of sugarcane straw covering the soil reduced water loss (0-20 cm layer) by approximately half when compared to uncovered soil.…”
Section: Ii) Crop Residues Vs Soil Physical Propertiesmentioning
confidence: 99%
“…In general, both treatments that retained straw (i.e., straw cover, raked) enhanced N and P concentrations in the plant tissue both early and late in the second ratoon. Increased plant nutrient concentrations may reflect the benefits of retaining straw, such as enhanced nutrient cycling (Sousa Jr. et al, 2018) and/or increased C accumulation (Galdos et al, 2017;Cherubin et al, 2018;Sousa Jr. et al, 2018), water storage and infiltration (Valim et al, 2016;Anjos et al, 2017), and biological activity (Paredes Jr. et al, 2015). Healthy soils generally have increased availability of N and P for plant uptake, which subsequently increases plant tissue concentrations of these elements when straw is retained.…”
Section: Second Ratoon Plant Nutrient Statusmentioning
confidence: 99%
“…The main changes caused by straw on the soil surface are the following: greater efficiency in the control of erosion and increase of the organic matter content, macro and microfauna, improving the soil structure, alteration in the incidence of light on the surface; increased infiltration of water into the soil; decrease in thermal amplitude and evaporation, especially in the superficial layers (INMAN-BAMBER;SMITH, 2004;GARCIA et al, 2007;CHRISTOFFOLETI et al, 2007;CAVENAGHI et al, 2007;GUIMARÃES et al, 2008;TAVARES et al, 2010;COSTA et al, 2014;PAREDES JUNIOR et al, 2015;VALIM et al, 2016).…”
Section: Introductionmentioning
confidence: 99%